If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 = -8y + 3(y + -2) Reorder the terms: -16 = -8y + 3(-2 + y) -16 = -8y + (-2 * 3 + y * 3) -16 = -8y + (-6 + 3y) Reorder the terms: -16 = -6 + -8y + 3y Combine like terms: -8y + 3y = -5y -16 = -6 + -5y Solving -16 = -6 + -5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5y' to each side of the equation. -16 + 5y = -6 + -5y + 5y Combine like terms: -5y + 5y = 0 -16 + 5y = -6 + 0 -16 + 5y = -6 Add '16' to each side of the equation. -16 + 16 + 5y = -6 + 16 Combine like terms: -16 + 16 = 0 0 + 5y = -6 + 16 5y = -6 + 16 Combine like terms: -6 + 16 = 10 5y = 10 Divide each side by '5'. y = 2 Simplifying y = 2
| 1=x/231 | | 98x+126=98 | | -3/7x+1/3=-1/2 | | -5w+29=2(w-3) | | 10x^2-6xy+y^2-25=0 | | 10x^2-6xy+y^2=25 | | 6(u+4)=-2u+40 | | -3v+42=-5(v-8) | | 64000=x(1-0.3) | | 26=3y-16 | | 9x+24=2x+3 | | 4cos^2x+3cosx=0 | | 158=67-x | | 16y=0.6y | | -4=y-7 | | -5a-(3a-7)= | | x^2-2x+8=20 | | b(y-b)=d(y-d) | | -5a-3a-7= | | -2+3(-6y-7)=-5(-5y-1)+2 | | 6=3+y | | x^2+3x-7=32 | | x^2+x+10=35 | | x^2+3x+4=16 | | x+10=24-x | | x^2+x-7=3 | | x^2+x-7=14 | | 0=44x^2-88x+74 | | 0=44x^2-88t+74 | | x^3+3=14 | | 24=4m | | -7(2x+3)+11x= |